PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL) TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA KELAS VIII SMP IT NURUL HIKMAH PENAJAM PASER UTARA: Materi Getaran, Gelombang dan Bunyi - Saputro, Luki Dwi Agung; Komariyah, Laili; Damayanti, Puardmi (JURNAL PEMBELAJARAN FISIKA, 2024)
The project based learning model (PjBL) is a learning model that directs students to play an active role in an activity to complete a certain learning project in accordance with the learning objectives to be achieved. This study aims to determine the effect of the application of the Project Based Learning (PjBL) learning model on the creative thinking ability of grade VIII students of SMP IT Nurul Hikmah Penajam Paser Utara. This type of research uses a quantitative approach with the Pre Experiment Design method is One Group Pretest-Postest. The sample used was 31 students of grade VIII B. Data collection uses technical tests in the form of 10 essay questions. The data analysis techniques used in this study are Normality Test Analysis, Normalize Gain (N-Gain) and Paired Sample T-test. The results showed that the application of the Project Based Learning (PjBL) learning model affected students' creative thinking skills with an N-Gain score of 0.72 in the high category. The Project Based Learning (PjBL) learning model is suitable to be used to improve students' creative thinking skills on vibration, wave and sound materials. Keywords: Project Based Learning (PjBL), Creative Thinking Ability.